TINJAUAN YURIDIS WANPRESTASI TERHADAP ISI PERJANJIAN PERKAWINAN OLEH PARA PIHAK - Ni Luh Virgina Nanda Dewi (JURNAL ILMU HUKUM TOPOSANTARO, 2025)
The purpose of this research: To find out the legal consequences in the event of default on the contents of the marriage agreement by the parties. To find out the legal remedies for default on the contents of the marriage agreement by the parties. The type of research used by the author is the Normative Legal Research Method. The conclusion in this research: The legal consequences in the event of default on the contents of the marriage agreement by the parties are that the party that has the impact of loss has the right to make a lawsuit demanding compensation for default involving material and immaterial aspects. Other legal consequences can file a divorce lawsuit if there is a default on the contents of the marriage agreement. Violation of the marriage agreement can trigger a lawsuit to cancel the agreement, with sanctions such as paying compensation or canceling the agreement. Legal remedies can be taken through litigation or non-litigation. The litigation route involves the courts, while non-litigation involves alternative dispute resolution. Non-litigation settlement efforts become alternative dispute resolution before going to court. The aim is to reach an agreement that benefits both parties and avoid divorce. Tujuan dalam penelitian ini: Untuk mengetahui akibat hukum apabila terjadi wanprestasi terhadap isi perjanjian perkawinan oleh para pihak. Untuk mengetahui upaya hukum wanprestasi terhadap isi perjanjian perkawinan oleh para pihak. Jenis penelitian yang digunakan penulis adalah Metode Penelitian Hukum Normatif. Kesimpulan dalam penelitian ini: Akibat hukum apabila terjadi wanprestasi terhadap isi perjanjian perkawinan oleh para pihak adalah pihak yang berdampak kerugian berhak membuat gugatan menuntut ganti rugi karena wanprestasi yang melibatkan aspek materiil dan inmateriil. Akibat hukum lainnya dapat mengajukan gugatan perceraian jika terjadi wanprestasi terhadap isi perjanjian perkawinan. Pelanggaran perjanjian kawin dapat memicu gugatan pembatalan perjanjian, dengan sanksi seperti membayar ganti rugi atau pembatalan perjanjian. Upaya hukum dapat diambil melalui litigasi atau non-litigasi. Jalur litigasi melibatkan pengadilan, sementara non-litigasi melibatkan alternatif penyelesaian sengketa. Upaya penyelesaian non-litigasi menjadi alternative penyelesaian sengketa sebelum masuk ke jalur pengadilan. Tujuannya adalah mencapai kesepakatan yang menguntungkan kedua belah pihak dan menghindari perceraian.